Towards transformative justice for un-coerced adult female sex workers in South Africa : an approach that speaks to the multi-layered and multi-faceted realities of women in South Africa - Lourens, Marna (Stellenbosch : Stellenbosch University, 2024)
Thesis (LLD)--Stellenbosch University, 2024.